Community Empowerment in Rural Areas Based on Social Capital in Lamongan Regency: A Holistic and Collaborative Approach - Nalikan, Mohammad; ., Sumartono; ., Suryadi; Rozikin, Mochammad (Journal of Ecohumanism, 2025)
This study aims to analyze the implementation of community empowerment in rural areas of Lamongan Regency through a social capital-based approach, utilizing holistic and collaborative strategies. The primary focus is to understand the role of social capital—comprising bonding, bridging, and linking dimensions—in community empowerment, while also evaluating the engagement of pentahelix stakeholders: government, society, academia, media, and the private sector. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observations, and document analysis. The findings reveal that leveraging social capital significantly contributes to social harmony, economic capacity building, and improved access to essential services. However, optimizing private sector participation and integrating cross-sectoral programs remain key challenges. Furthermore, the proposed social capital-based community empowerment model underscores the importance of stakeholder synergy in achieving sustainable rural development. The study has implications for regional development policies, advocating for an inclusive, poverty-alleviation-oriented, and locally driven empowerment approach.